Water and women: passage rite´s cyclicity in Única mirando al mar by Fernando Contreras - Campos Rodríguez, Delia (2019)
This investigation made an approach to the symbolic framework around water and any of its forms in the novel “Única mirando al mar” by Fernando Contreras Castro, in order to recognize the present relationship between water, and its cyclical notion, with the also cyclical conception that archetypally falls on women in passage moments and rites. In conclusion, in this text metaphors and allusions to water are used to create an aura of sacredness in a completely profane environment, which allows the offering of rose petals to the sea as a representation of the protagonist recovering her son. Therefore, Única, in the novel, not only looks at the sea, but she is the sea, because women and water are symbolically united, forever cyclical and changing.